Secure Seaport Management System using Blockchain Technology - Hamad, Ali H. (Al-Khwarizmi Engineering Journal, 2023)
Worldwide, shipping documents are still primarily created and handled in the traditional paper manner. Processes taking place in shipping ports as a result are time-consuming and heavily dependent on paper. Shipping documents are particularly susceptible to paperwork fraud because they involve numerous parties with competing interests. With the aid of smart contracts, a distributed, shared, and append-only ledger provided by blockchain technology allows for the addition of new records. In order to increase maritime transport and port efficiency and promote economic development, this paper examines current maritime sector developments in Iraq and offers a paradigm to secure the management system based on a hyper-ledger fabric blockchain platform. The performance evaluation of the proposed system implies two scenarios: one organization and two organizations by examining throughput and latency. High transaction transmission rates on large block sizes produced positive results. Similarly, employing a small block size and higher send rates results in poor performance. Additionally, it was noted that throughput will decrease and latency will rise as the number of organizations increases. Block size and block timeouts should be high in applications with many concurrent transactions in order to maintain good throughput.